Me and the boss : [book with audioplayer] a story about mending and love - Edwards, Michelle (Findaway World, LLC, 2023)
Six-year-old Lee will not give up until he can show his big sister Zora, a.k.a. the boss, how good he can sew. Includes instructions on how to make Lee's smiling moon.